Effect of periphery fixity on ballistic limit of thin aluminum plate subjected to blunt and ogival projectile impact - Tiwari, Gaurav; Iqbal, M.A.; Gupta, Pramod K. (Zielona Góra: Uniwersytet Zielonogórski)
Three-dimensional numerical simulations were carried out with the ABAQUS/explicit finite element code to study the influence of target boundary conditions on its ballistic limit. 1mm thick 1100-H12 aluminum target of 255 mm span diameter was hit by 19 mm diameter and 50.8 mm length blunt nosed projectile. The mass of the projectile was kept as 52.5 gm. The boundary condition effects on the ballistic limit were investigated by varying the target periphery boundary condition as fully clamped and partially clamped target (75%, 50% and 25%) subjected to projectile impact. The energy absorption and ballistic limit of the target was found to be significantly affected by the boundary conditions. Some of the finite element analysis results were compared with experimental and numerical results reported in international literature and a good agreement between the two was found.
Keywords: periphery fixity; blunt nosed projectile; ABAQUS